Design fiction for mixed-reality performances - Rostami, Asreen; Rossitto, Chiara; Barkhuus, Louise; Hook, Jonathan; Laaksolahti, Jarmo; Taylor, Robyn; McMillan, Donald; Spence, Jocelyn; Williamson, Julie (2017)
Designing for mixed-reality performances is challenging both in terms of technology design, and in terms of understanding the interplay between technology, narration, and (the outcomes of) audience interactions. This complexity also stems from the variety of roles in the creative team often entailing technology designers, artists, directors, producers, set-designers and performers. In this multidisciplinary, one-day workshop, we seek to bring together HCI scholars, designers, artists, and curators to explore the potential provided by Design Fiction as a method to generate ideas for Mixed-Reality Performance (MRP) through various archetypes including scripts, programs, and posters. By drawing attention to novel interactive technologies, such as bio-sensors and environmental IoT, we seek to generate design fiction scenarios capturing the aesthetic and interactive potential for mixed-reality performances, as well as the challenges to gain access to audience members’ data – i.e. physiological states, daily routines, conversations, etc.